INMTD: Intent-based Moving Target Defense Framework using Software Defined Networks - Hyder, M. F.; Ismail, M. A. (Engineering, Technology & Applied Science Research, 2020)
Intent-Based Networking (IBN) is an emerging networking paradigm while Moving Target Defense (MTD) is an active security technique. In this paper, the Intent-based Moving Target Defense (INMTD) framework using Software Defined Networks is proposed. INMTD is the first effort in exploiting IBN for the design of an efficient Moving Target Defense (MTD) framework. INMTD uses the concept of shadow servers in order to counter the first stage of cyber-attacks, i.e. reconnaissance attacks targeted against servers running in SDN networks. INMTD comprises of an MTD application running on an SDN controller. The MTD application has reconnaissance detection, MTD movement, and MTD monitoring modules. The MTD application is integrated with the intent-based northbound API of SDN controller. INMTD not only provides protection against probing attacks, but it also provides high availability due to shadow servers. The proposed framework was implemented using Mininet and ONOS SDN controller. The proposed framework was assessed in terms of defender cost, attacker’s effort, and introduced complexity in the system. The results substantiate the efficient protection against reconnaissance attacks at lower computational cost.